2011
DOI: 10.1007/s00547-003-0942-1
|View full text |Cite
|
Sign up to set email alerts
|

N-glycoforms of serum alpha-1-acid glycoprotein in patients with lower limb chronic arterial ischaemia

Abstract: Alterations of serum acute phase proteins (APP) N-glycosylation are observed in various necrotic and inflammatory processes. In artherosclerotic chronic arterial ischaemia of the lower extremities, such alterations have not been reported. N-glycoforms of representative APP, alpha-1-acid glycoprotein (AGP), interleukin-6 (IL-6) and soluble IL-6 receptor (sIL-6R), involved in regulation of APP N-glycosylation, were studied in 42 patients sera. Twelve patients had moderate, and 30 had critical ischaemia. In 35 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Ceruloplasmin was reduced in Group D in intra-group comparisons at 20 minutes and two hours after the tourniquet was released. In the previous study a correlation between ceruloplasmin, ceruloplasmin oxidase activity and lower limb ischemia level was found [31]. But in this study the other oxidative and anti-oxidative markers which were specific for ischemia were evaluated no changes were detected at the intra-group comparisons in both groups.…”
Section: Discussionmentioning
confidence: 56%
“…Ceruloplasmin was reduced in Group D in intra-group comparisons at 20 minutes and two hours after the tourniquet was released. In the previous study a correlation between ceruloplasmin, ceruloplasmin oxidase activity and lower limb ischemia level was found [31]. But in this study the other oxidative and anti-oxidative markers which were specific for ischemia were evaluated no changes were detected at the intra-group comparisons in both groups.…”
Section: Discussionmentioning
confidence: 56%
“…Elevated Cu concentrations in atherosclerotic plaque have also been reported [41]. Furthermore, an increase in Cu concentration, mainly due to an increase in oxidase activity and ceruloplasmin levels, has been observed in both serum and arterial walls in atherosclerosis [72]. The statistically lower 31 P levels in group A may indicate that soluble Ca carbonates and oxalates, rather than phosphates such as calcium hydroxyapatite, are involved in the calcification process.…”
Section: Atherosclerosis Vs Steatosis Mineral Difference In the Brainmentioning
confidence: 92%
“…In recent years, research has increasingly focused on the accumulation of these and other elements in tissues. In the case of ATH, which is a vascular disease, elevated serum and arterial wall Cu levels, and increased oxidase and ceruloplasmin activities, have been observed [72]. In the work of Hanć et al [41], an accumulation of Cu, together with Zn, Ca, Mg, and Pb, was also observed in atherosclerotic plaque samples.…”
Section: Atherosclerosis Vs Hepatic Steatosis-the Mineral Difference ...mentioning
confidence: 97%